2002
DOI: 10.1002/1521-4141(200207)32:7<2004::aid-immu2004>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

BAFF is a survival and maturation factor for mouse B cells

Abstract: Human B cell‐activating factor (BAFF) induces mouse surface IgM+ B cells of the immature type from bone marrow and of the immature types 1 and 2 from spleen, as well as of the mature type from spleen to increased longevity in tissue culture. BAFF does so polyclonally and without inducing proliferation in any of these B cell subpopulations. BAFF induces phenotypic and functional maturation of immature to mature B cells so that all immature cells loose C1qRp (AA4.1, 493) expression and type 1 immature cells up‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(102 citation statements)
references
References 45 publications
7
95
0
Order By: Relevance
“…BAFF is a B cell survival factor for transitional type-2 and other B cells in vitro [17,18,23]. In vivo, absence of BAFF signaling results in a severe deficit of mature B cells in BAFF -/-, BAFF-R-deficient and TACI-Ig-Tg mice [2-4, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAFF is a B cell survival factor for transitional type-2 and other B cells in vitro [17,18,23]. In vivo, absence of BAFF signaling results in a severe deficit of mature B cells in BAFF -/-, BAFF-R-deficient and TACI-Ig-Tg mice [2-4, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Results from in vitro studies rather suggest that BAFF acts as a survival factor on transitional and mature B cells [17,18]. However, the study of BAFF function on follicular or marginal zone B cells in vivo is hampered by the fact that their precursors depend on BAFF.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BLyS has been implicated in several humoral autoimmune disorders and animal models of autoimmunity (13)(14)(15)(16), confirming its function in specificity-based selection. We and others have shown that mature B cells continuously compete for BLyS to survive (10), and that BLyS levels determine the proportion of cells that successfully complete transitional B cell differentiation (4,(17)(18)(19). Among the three known BLyS receptors, BLyS receptor 3 (BR3) interacts solely with BLyS and plays a dominant role in maintaining normal follicular (FO) and marginal zone (MZ) B cell numbers (8,9,11,20,21).…”
Section: Tlr Stimulation Modifies Blys Receptor Expression Inmentioning
confidence: 99%
“…[30][31][32][33] In vivo and in vitro studies have demonstrated that BLyS signaling increases the expression of antiapoptotic molecules such as Bcl-2 and promotes cell survival, cell-cycle progression, and proliferation of B cells. [34][35][36][37] Previous studies also have shown that BLyS can activate NF-B2 through the ubiquitin-mediated proteolysis of p100, 27,28 and the NF-B1 pathway through the proteolysis of IB␣ in vitro. 35,38 These studies suggest that activation of NF-B family members play a major role in critical BLyS signaling pathway in the mature B-cell lineage.…”
Section: Introductionmentioning
confidence: 99%